2018
DOI: 10.1002/pds.4649
|View full text |Cite
|
Sign up to set email alerts
|

Exposure measurement error when assessing current glucocorticoid use using UK primary care electronic prescription data

Abstract: Purpose To quantify misclassification in glucocorticoid (GC) exposure defined using UK primary care prescription data. Methods A cross‐sectional study including patients with rheumatoid arthritis prescribed oral GCs in the past 2 years. Glucocorticoid exposure based on electronic prescription records was compared with participant‐reported GC use captured using a paper diary. Prescription data (containing information about prescriptions issued but no dispensing information) was provided by the Clinical Practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…When defining medication-exposed comparison groups, more than half of the reviewed studies relied partly or entirely on self-reported medication use during pregnancy [29,35,37,38,43,[45][46][47][48]51]. This measure does not necessarily reflect the actual medication use [66][67][68] and is vulnerable to recall bias if reported retrospectively [69]. In five studies, medication exposure was assessed at birth using maternal and/or neonatal blood concentrations of the medication [31,34,37,47,51].…”
Section: And Pt 3 Box 1)mentioning
confidence: 99%
“…When defining medication-exposed comparison groups, more than half of the reviewed studies relied partly or entirely on self-reported medication use during pregnancy [29,35,37,38,43,[45][46][47][48]51]. This measure does not necessarily reflect the actual medication use [66][67][68] and is vulnerable to recall bias if reported retrospectively [69]. In five studies, medication exposure was assessed at birth using maternal and/or neonatal blood concentrations of the medication [31,34,37,47,51].…”
Section: And Pt 3 Box 1)mentioning
confidence: 99%
“…3 Large administrative health databases typically record only drug dispensations and not their actual use, which can lead to biased estimates and even spurious conclusions. 64 In general, some un-observed discrepancies between daily doses actually taken by a patient and the expected dose, reconstructed from the CPRD prescriptions database, are likely to occur due to a variety of patient-specific patterns of total or partial treatment non-adherence, and probably attenuated the strength of the estimated association. 64,65 In contrast, the measurement errors in the outcome are unlikely to have a material impact on our results as, in clinical practice, the body weight is typically measured with absolute errors of only 0.4–0.6 kg.…”
Section: Discussionmentioning
confidence: 99%
“…These data were often missing when prescriptions were issued with information restricted to the free-text field, such as ‘Take as indicated by your dermatologist’. Implausible and missing values were handled using the DrugPrep algorithm, 28 with the decisions described and validated by Joseph et al 29 (see Supplementary Table S2). Cleaning oral glucocorticoid prescriptions in this way has been found to have a sensitivity of 84.2% (95% CI = 68.7% to 94.0%) and a specificity of 87.5% (95% CI = 73.2% to 95.8%) for predicting patient-reported current glucocorticoid use.…”
Section: Methodsmentioning
confidence: 99%
“…Cleaning oral glucocorticoid prescriptions in this way has been found to have a sensitivity of 84.2% (95% CI = 68.7% to 94.0%) and a specificity of 87.5% (95% CI = 73.2% to 95.8%) for predicting patient-reported current glucocorticoid use. 29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation